2019
DOI: 10.1007/s11295-019-1324-y
|View full text |Cite
|
Sign up to set email alerts
|

Two large-effect QTLs, Ma and Ma3, determine genetic potential for acidity in apple fruit: breeding insights from a multi-family study

Abstract: Acidity is a critical component of the apple fruit consumption experience. In previous biparental family studies, two large-effect acidity QTLs were reported using freshly harvested fruit. Objectives of this study were to determine the number and location of QTLs for acidity variation in a large apple breeding program and ascertain the quantitative effects and breeding relevance of QTL allelic combinations at harvest and after commercially relevant periods of cold storage. Pedigree-connected germplasm of 16 fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
83
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 70 publications
18
83
1
Order By: Relevance
“…5). These data confirm the relationship between Ma1 genotypes and fruit acidity and the incomplete dominance of Ma1 over ma1 reported earlier (Bai et al, 2012;Xu et al, 2012) and from subsequent investigations by other groups on different segregating populations (Khan et al, 2013;Jia et al, 2018;Verma et al, 2019) as well as over a wide range of Malus accessions (Ma et al, 2015). In addition, RNAi suppression of Ma1 expression in 'McIntosh' apple leaves, 'Empire' apple fruit, and 'Orin' calli significantly decreased the malate level ( Fig.…”
Section: Premature Stop Codon-led Mutation Is Genetically Responsiblesupporting
confidence: 89%
See 2 more Smart Citations
“…5). These data confirm the relationship between Ma1 genotypes and fruit acidity and the incomplete dominance of Ma1 over ma1 reported earlier (Bai et al, 2012;Xu et al, 2012) and from subsequent investigations by other groups on different segregating populations (Khan et al, 2013;Jia et al, 2018;Verma et al, 2019) as well as over a wide range of Malus accessions (Ma et al, 2015). In addition, RNAi suppression of Ma1 expression in 'McIntosh' apple leaves, 'Empire' apple fruit, and 'Orin' calli significantly decreased the malate level ( Fig.…”
Section: Premature Stop Codon-led Mutation Is Genetically Responsiblesupporting
confidence: 89%
“…Third, a QTL originally identified in the cross 'Fiesta' 3 'Discovery' on linkage group 8 was recently confirmed in pedigree-connected germplasm of 16 full-sib families representing nine important breeding parents. This QTL was named Ma3 and also plays a significant role in determining malate accumulation in apple (Liebhard et al, 2003;Verma et al, 2019). Ma3 and Ma1 follow an additive allele dosage model and jointly explain about 66% of the variation in apple fruit acidity (Verma et al, 2019).…”
Section: Premature Stop Codon-led Mutation Is Genetically Responsiblementioning
confidence: 99%
See 1 more Smart Citation
“…The approach can potentially increase the QTL detection power and the accuracy of QTL positioning (Liu, Reif, Ranc, Porta, & Wurschum, 2012) and provide knowledge that is more applicable to marker-assisted selection on critical loci and alleles over a range of genetic backgrounds (Bink et al, 2014). Verma et al (2019) and van de Weg et al (2018) identified large-effect QTLs determining the acidity and resistance to fire blight in apple fruit (Malus spp. ), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Q2 had a less strong effect and was present in each of our parents, underlining its general occurrence in our breeding program. The use of multiparent populations for finding multiple functional alleles of different effect was also reported for two acidity QTLs/genes in apple by [30].…”
Section: Blushmentioning
confidence: 82%